Atherosclerosis Susceptibility in Mice Is Independent of the V1 Immunoglobulin Heavy Chain Gene. Issue 1 (January 2016) - Centa, Monica; Gruber, Sabrina; Nilsson, Daniel; Polyzos, Konstantinos A.; Johansson, Daniel K.; Hansson, Göran K.; Ketelhuth, Daniel F.J.; Binder, Christoph J.; Malin, Stephen
Abstract : Objective—: The V1 ( V H S107.1.42 ) immunoglobulin heavy chain gene is thought to be critical in producing IgM natural antibodies of the T15-idiotype that protect against both atherosclerosis and infection from Streptococcus pneumoniae . Our aim was to determine whether genetic loss of the V1 gene increased atherosclerotic plaque burden in vivo because of a reduction in the T15-idiotype or other atheroprotective antibodies. Approach and Results—: We crossed V H S107.1.42 -deficient mice with the atherosclerosis-prone Apoe −/− and Ldlr −/− strains. Although these double knockout strains manifested no defects in B-cell development, we did observe a substantial reduction in early immune responses against phosphocholine after immunization. However, the titers of plasma antibodies reacting against defined atherosclerotic antigens such as oxidized low-density lipoprotein, as well as the T15-idiotype, were unaffected by loss of the V H S107.1.42 gene in hypercholesterolemic mice. Furthermore, we observed no increase in atherosclerotic lesion formation, either within the aortic arch or aortic root. Robust deposition of IgM within atherosclerotic plaques could also be readily observed in both control and experimental mice. Conclusions—: Our data indicate that IgM-dependent protection against atherosclerosis is unlikely to be dependent on antibodies that use the V H S107.1.42 gene, in contrast to the acute immune response conferred by this heavy chain in the response to phosphocholine and in providing resistance against lethal S pneumoniae infection. Abstract : Supplemental Digital Content is available in the text.